2021
DOI: 10.1002/pssr.202100197
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Reversal Process in 3D Permalloy Nanomatrix

Abstract: A 3D matrix created by self-alignment of nanowires and 2D antidots is reported. Interactions between nanowires and antidots leading to non-conventional magnetic properties in the 3D matrix are reported. While the easy-axis magnetization of the 3D matrix is dominated by shape anisotropy of the nanowires, the hard-axis magnetization reversal behavior is driven by the bottom 2D antidots. Detailed analysis reveals a defect-induced domain wall propagation process for the easy-axis-reversal process. Micromagnetic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The procedure for the magnetization reversal study is reported in detail in our previous literature. [ 26 ] The black arrows indicate the direction of the applied field. The white dotted rectangles show the location of the HGS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The procedure for the magnetization reversal study is reported in detail in our previous literature. [ 26 ] The black arrows indicate the direction of the applied field. The white dotted rectangles show the location of the HGS.…”
Section: Resultsmentioning
confidence: 99%
“…These observed magnetic domain states for the easy‐axis reversal are similar to previously reported magnetic domain states of conventional 2D antidot matrix. [ 26,27 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations